Perovskitas do tipo LaNixCo1-xO3 suportadas em SBA-15 como precursores de catalisadores Ni-Co aplicados à reforma a vapor do etanol - Costa, Isa Carolina Silva (Universidade Federal de São Carlos, 2018)
The production of hydrogen from the steam reforming process of ethanol stands out as a process for the diversification of the world energy matrix, which aims to reduce environmental impacts and ensure energy security. Among the catalysts already evaluated for this process, those based on metals such as Ni and Co are active for the reaction, but can be deactivated by the formation of carbon on the surface and sintering of the metal particles. Among the strategies to increase the performance and stability of these catalysts, the synthesis from perovskite precursors (ABO3) makes it possible to obtain metals (B) highly dispersed in oxides (AOx). However, the compounds obtained from these structures have low surface area, which decreases the active surface of the material. To study the effects of the nature and composition of the catalysts and the increase of the specific area, Ni, Co and Ni-Co catalysts obtained from LaNixCo1-xO3 and LaNixCo1-xO3/SBA-15 perovskites were prepared and applied to the reform to the ethanol vapor. In order to define a synthesis method for the formation of perovskites on the mesoporous support SBA-15, the precursor materials were synthesized from impregnations based on the modified Pechini and amorphous citrate methods. The synthesis of perovskites on SBA-15 from impregnation based on the modified Pechini method showed less tendency to form secondary phases. The Ni catalyst obtained from the reduction of this material presented higher activity and yield for H2 production when compared to that obtained by the amorphous citrate method. From this method, materials with different proportions of perovskite on the support and mass perovskites were prepared. The increase of the perovskite ratio on the support indicated a higher formation of segregated NiO and less dispersion of the active phase. The catalytic activity and the rate of carbon formation, however, were similar among the materials, even in view of the increase in the metallic percentage. The introduction of Co into the B site of the perovskite structure leads to the reduction of the formation of secondary phases, due to the higher stability, that perovskite with the insertion of this cation in its crystalline lattice happens to present. The catalysts with Ni-Co and Co showed lower activity for the reaction, but the rate of carbon formation decreased, due to the lower Co activity in the C-C bond breakage and its greater ability to activate the water. Comparison of the performance of the supported catalysts with those synthesized from the perovskite masses showed increased catalytic activity and reduced carbon formation in the materials supported in SBA-15, due to the greater dispersion of the active phase.
LaNixCo1-xO3 perovskite-type oxides supported on SBA-15 as precursors of Ni-Co catalysts applied to steam reforming of ethanol
Keywords: Perovskita; Etanol; Reforma a vapor; Perovskite; Ethanol; Steam reforming; ENGENHARIAS::ENGENHARIA QUIMICA